2016
DOI: 10.1002/pbc.26086
|View full text |Cite
|
Sign up to set email alerts
|

Profound clinical and radiological response to BRAF inhibition in a 2‐month‐old diencephalic child with hypothalamic/chiasmatic glioma

Abstract: Infants with low-grade glioma (LGG) have a poor survival. BRAFV600E mutation has been identified in pediatric LGG; however, the use of BRAF inhibitors in infants has never been reported. A 2-month-old with V600E mutant hypothalamic/chiasmatic glioma progressed on chemotherapy resulting in profound visual loss, massive ascites, and diencephalic syndrome. Initiation of dabrafenib resulted in rapid and sustained disappearance of clinical symptoms and a profound sustained cytoreduction. BRAF inhibition was safely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 21 publications
2
47
1
3
Order By: Relevance
“…Lassaletta et al. have shown that BRAF V600E inhibition is feasible in very young infants already and others have shown that responses can be observed early in LGG . In contrast to the relapse after 1 year after cessation of BRAF V600E inhibition described in the present case, rebounds appearing very soon (<3 months) have been reported and also been successfully retreated .…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Lassaletta et al. have shown that BRAF V600E inhibition is feasible in very young infants already and others have shown that responses can be observed early in LGG . In contrast to the relapse after 1 year after cessation of BRAF V600E inhibition described in the present case, rebounds appearing very soon (<3 months) have been reported and also been successfully retreated .…”
Section: Discussioncontrasting
confidence: 57%
“…Low‐grade glioma (LGG) is considered a single pathway disease of the MAPK pathway, which makes LGG an attractive candidate for targeted treatments. Sustained responses have been reported in patients with BRAF V600E mutated tumors treated with BRAF V600E inhibitors, as has been observed with MEK inhibition in LGG with BRAF‐KIAA fusions …”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…BRAF inhibitors, including vemurafenib and dabrafenib, have proved successful either alone or in conjunction with trametinib, an inhibitor of another MAPK member MEK, to treat adults with papillary craniopharyngioma, resulting in tumor shrinkage with good tolerability [2,5,24,25]. In addition, increasing pediatric data is emerging for BRAF and MEK inhibitors in the treatment of surgically inaccessible gliomas that express BRAF V600E mutations, with an acceptable side effect profile in this age group [1,3,4,16,18,29]. While initial results are promising, long-term safety data is lacking as is knowledge on the longevity of therapy required.…”
Section: Discussionmentioning
confidence: 99%